Liberalism's Crooked Circle : Letters to Adam Michnik - Katznelson, Ira (Book collections on Project MUSE., 1996)
Katznelson's first letter explores how the virtues of socialism, including its moral stand on social justice, can be related to liberalism while overcoming debilitating aspects of the socialist inheritance. The second asks whether liberalism can recognize, appreciate, and manage human difference. Situated in the lineage of efforts by Richard Hofstadter, C. Wright Mills, and Lionel Trilling to "thicken" liberalism, these letters also draw on personal experience in the radical politics of the 1960s and in the dissident culture of East and Central Europe in the years immediately preceding communism's demise.